Evaluasi Karakteristik Parkir pada Area Parkir Mobil di Fakultas Teknik Sipil dan Perencanaan (FTSP), Universitas Islam Indonesia - Hadi, Muhamad Abdul; Bintang, Muhammad Kennyzyra (Borneo Engineering : Jurnal Teknik Sipil, 2024)
FTSP UII has a high number of academic activities. High academic activity will affect to supporting facilities such as parking facilities. One of the problems with parking facilities is the lack of parking capacity. This study aims to determine the characteristics of car parking in the FTSP UII area both on the road and outside the road and determine the improvement efforts that can be made. The analysis conducted in this study is guided by the Parking Technical Guidelines made by the Directorate General of Land Transportation (1996). Based on the analysis that has been done, it is concluded that in every parking area located outside the road body, the load value of the parking area is below 85%. Furthermore, in parking areas located on the body of the road, parking areas 1B-B and parking areas 2B-A have parking area load values above 90%. While parking area 1B-A and parking area 2B-B have a parking area load value below 90%. Improvement efforts for parking areas outside the road body are by arranging routes to the parking area and reusing unused parking areas. As for the parking area on the road body, it is planned to add a new parking area considering that there is a parking area that has a parking load of 90% and there is a parking area with unsafe parking index conditions. Thus, the addition of this parking area is expected to reduce the parking load on parking areas on the road body whose value exceeds 90%.